Effects of Frangipani Flower Extract (Plumeria acuminata L.) Against the Mortality of Aedes aegypti Larvae - Lidya, Eka; Yushananta, Prayudhy (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2024)
Bioinsecticide development has become a demand after the adverse effects of long-term use of synthetic chemical insecticides, including vector resistance and environmental pollution. In particular, this study investigated the ability of Frangipani flower extract (Plumeria acuminata L.) as larvacidal against Aedes aegypti instar III. The study used a Factorial Completely Randomized Design (two replications), conducted on March-May 2023. Plant extraction by maceration using 96% ethanol solvent. Bioassay tests were carried out at three concentration levels (5%, 7%, 10%) and four levels of contact time (6, 12, 18, 24 hours), with 25 larvae in each treatment. Spectrophotometry methods measured flavonoid and saponin content. The two-way ANOVA test analyzed data, the Tukey test, and the probit test to obtain LC50 and LC90. The study found flavonoid and saponin content of 4.43 Mg QE/g and 2.45%, respectively. The lowest total mortality (24 hours after exposure) of Aedes aegypti larvae was at a concentration of 5% (MR= 58%) and highest at concentrations of 7% and 10% (MR= 100%). The 7% concentration is the best performance as a larvicide. Statistical analysis showed differences in mortality based on concentration (P = 0.0001) and contact time (P = 0.0001). Mortality of larvae was caused by damage to the respiratory and digestive systems, as seen from the lateral hair, siphon, and abdomen condition. The results of the probit test obtained LC50 and LC90 of 4.85% (4.36–5.10%) and 5.86% (5.49-7.20%), respectively. The study has proven that Plumeria acuminata L. flower extract has the potential as a biolarvaside against Aedes aegypti, with a mortality effect reaching 100% after 24 hours of exposure.